2022
DOI: 10.1097/md.0000000000031903
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial removal of the peripherally located foreign body with the ultrathin bronchoscopy and ultrathin cryoprobe guided by a manual navigating method: A case report

Abstract: Rational:The bronchoscope is a preferential method used to remove airway foreign bodies, but for those located in the distal lumen of bronchus with long-time retention, how to remove them remains an intractable problem.Patient concerns: A 57-year-old male presented with 2-week history of intermittent hemoptysis. Chest CT upon admission revealed a high-density opacity incarcerated in the distal basal segment of the left lower lobe, along with obstructive pneumonia.Diagnoses: The patient was diagnosed as foreign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, if the fish is deeper in the airway, this method may be less effective. Previous studies [ 12 ] have demonstrated that using an ultra-thin bronchoscope combined with an ultra-thin freezing probe under artificial navigation can effectively remove foreign bodies in the distal bronchus. Second, the fish in this case has a soft texture, making it easier to be suctioned out using a negative pressure suction device connected to the tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the fish is deeper in the airway, this method may be less effective. Previous studies [ 12 ] have demonstrated that using an ultra-thin bronchoscope combined with an ultra-thin freezing probe under artificial navigation can effectively remove foreign bodies in the distal bronchus. Second, the fish in this case has a soft texture, making it easier to be suctioned out using a negative pressure suction device connected to the tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%